2020
DOI: 10.3389/fonc.2020.523577
|View full text |Cite
|
Sign up to set email alerts
|

Baoyuan Jiedu Decoction Alleviates Cancer-Induced Myotube Atrophy by Regulating Mitochondrial Dynamics Through p38 MAPK/PGC-1α Signaling Pathway

Abstract: Cancer cachexia is a multifactorial syndrome characterized by continuous body wasting and loss of skeletal muscle. Impaired mitochondria function is closely associated with muscle atrophy in cancer cachexia. Our previous study confirmed the effectiveness of Baoyuan Jiedu decoction (BJD) in inhibiting cancer-induced muscle atrophy in an in vivo model. However, little is known about its mechanisms in regulating mitochondria dysfunction. In this study, we evaluated the therapeutic effect and action mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…All herbs were purchased from Zhonglu Hospital (Shandong, China) and identified by the professors from the Department of Pharmacy, Shandong University of Traditional Chinese Medicine (Shandong, China). The method of preparing extracts of BJD was consistent with the study we published previously (Wang et al, 2020), as hot water extracts from the six crude herbs that concentrated to 1.15 g drug/ml.…”
Section: Preparation Of the Extracts For Bjd And Hplc Conditionsmentioning
confidence: 80%
See 3 more Smart Citations
“…All herbs were purchased from Zhonglu Hospital (Shandong, China) and identified by the professors from the Department of Pharmacy, Shandong University of Traditional Chinese Medicine (Shandong, China). The method of preparing extracts of BJD was consistent with the study we published previously (Wang et al, 2020), as hot water extracts from the six crude herbs that concentrated to 1.15 g drug/ml.…”
Section: Preparation Of the Extracts For Bjd And Hplc Conditionsmentioning
confidence: 80%
“…C57BL/6 J mice were used as a blank control group (normal group). According to our previous study (Wang et al, 2020), the dose of the BJD group was 23 g/kgd by gavage. The MA group was intraperitoneally injected with 24 mg/kgd of megestrol acetate (Ape×Bio, United States, Cat# B1377).…”
Section: Micementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, peripheral inflammation and immune activation Meanwhile, palmitoylethanolamide is a fatty acid derivative that can antifatigue through inhibiting inflammation [ 36 ]. Notably, it has been reported that the treatment of Baoyuan Jiedu decoction involving indole-3-acrylic acid, isoliquiritigenin, formononetin, 18- β -glycyrrhetinic acid, and 9S,13R-12-oxophytodienoic acid prevented prominent myotube atrophy and regulated mitochondrial production [ 37 ]. Indeed, mitochondria and muscles are damaged with fatigue [ 38 ].…”
Section: Resultsmentioning
confidence: 99%